Cultura popular y cultura de masas. notas para debate - Amalia Signorelli (Estudios sobre las Culturas Contemporáneas)
What kind of relationship exists between mass culture and popular, local and class cultures? After examining a number of current interpretations, the author puts forward a hypothesis on the study of mass culture within the framework of a comparative interpretation of cultural relations on a world-wide scale, but strating from local and class manifestations of conflicts and oppositions. An examination structured in this way starts with the assumption of a critical revision of the concepts of class, masses, conscience, popular and conflict.